Determination of some properties of guar gum added chitosan based adhesives - İsmail Özlüsoylu; Mehmet Emin Ergün (Turkish Journal of Forestry, 2023)
Most of the adhesives used in the wood industry are fossil fuel-based and cause risks to the environment and human health, especially due to formaldehyde content. In order to reduce this negative situation, research on different methods to reduce formaldehyde emissions has been carried out in recent years. Among these research, the use of bio-based adhesives attracts attention, especially because of its positive properties in terms of health. This study investigated the potential of using natural polymers chitosan and guar gum as a wood adhesive. For this purpose, guar gum was incorporated into the chitosan-based adhesive in 4 different ratios (0.06%, 0.2%, 1%, and 2%). The impact of adding different amounts of guar gum on the binding strength was assessed by measuring the viscosity of the produced glue. In addition, Fourier transform infrared spectroscopy (FTIR) analysis was performed to examine the interaction of chitosan-based adhesives with wood. The viscosity of the chitosan-based adhesive with the addition of guar gum was found to be between 1380 CP and 5264 CP. It was found that the bond strength value of the chitosan-based adhesive with % 0.2 guar gum added improved by 88% compared to the group without guar gum. It was concluded that chitosan-based glue with guar gum added has positive properties especially with its environmentalist structure and can be used in different areas.